2012
DOI: 10.1371/journal.pone.0035980
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Adaptation of Bone-PDL-Tooth Complex: Rattus-Norvegicus as a Model System

Abstract: Functional loads on an organ induce tissue adaptations by converting mechanical energy into chemical energy at a cell-level. The transducing capacity of cells alters physico-chemical properties of tissues, developing a positive feedback commonly recognized as the form-function relationship. In this study, organ and tissue adaptations were mapped in the bone-tooth complex by identifying and correlating biomolecular expressions to physico-chemical properties in rats from 1.5 to 15 months. However, future researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 101 publications
(123 reference statements)
3
46
0
Order By: Relevance
“…Furthermore, we found that Asp, Lum, and Dcn responded to the depletion of Fmod and Bgn in an age-and tissue-specific manner, with Lum and Dcn uniformly enhanced in the PDL at 4 wk and Asp at 8 wk, more specifically in the PDL on the buccal side and the PDL near alveolar bone around the incisor. This variation in the distribution and relative content of SLRPs marks the physical-chemical changes translated from age-and function-related differences, as discussed in studies by the Ho group (Leong et al, 2012). Overall, our finding suggests that SLRPs cannot compensate completely for the function of one another, and further investigations are needed to identify the specific structural and functional roles of SLRPs at different stages of successive construction and remodeling of the ECM.…”
Section: Slrps Regulate Collagen Fibrillogenesis and Periodontal Homesupporting
confidence: 68%
“…Furthermore, we found that Asp, Lum, and Dcn responded to the depletion of Fmod and Bgn in an age-and tissue-specific manner, with Lum and Dcn uniformly enhanced in the PDL at 4 wk and Asp at 8 wk, more specifically in the PDL on the buccal side and the PDL near alveolar bone around the incisor. This variation in the distribution and relative content of SLRPs marks the physical-chemical changes translated from age-and function-related differences, as discussed in studies by the Ho group (Leong et al, 2012). Overall, our finding suggests that SLRPs cannot compensate completely for the function of one another, and further investigations are needed to identify the specific structural and functional roles of SLRPs at different stages of successive construction and remodeling of the ECM.…”
Section: Slrps Regulate Collagen Fibrillogenesis and Periodontal Homesupporting
confidence: 68%
“…It has been observed that type I collagen decreases in the periodontium with increasing age (Ohi et al 2006, Lim et al 2014). This phenomenon was recently reproduced by a study that identified a progressive atrophy of the tooth supporting structures associated with ageing in rats (Leong et al 2012). Another non-immune source of periodontal tissue deterioration associated with ageing relates to deficiencies in the wound healing response.…”
Section: The Complex Relationship Between Periodontal Tissue Destructmentioning
confidence: 88%
“…SLRPs regulate collagen fibrillogenesis by binding to specific sites of collagen molecules. Several SLRP family members have been identified in PDL [147,148]. The role of SLRPs in collagen fibrillogenesis and subsequent tissue conformation have been extensively studied in either single- or double-mutant transgenic mice [149].…”
Section: Small Leucine-rich Proteoglycans (Slrps)mentioning
confidence: 99%